CORRELATION BETWEEN CARBON DIOXIDE (CO2) AND RESPIRATORY ISSUES: A LITERATURE REVIEW - Krismanuel, Hari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
ABSTRACT The increasing levels of carbon dioxide (CO2) in the atmosphere due to human activities have raised concerns regarding potential health impacts, particularly on respiratory health. This literature review aims to examine the correlation between CO2 and respiratory issues by synthesizing the findings of relevant studies. A comprehensive search was conducted across academic databases, and studies were selected based on their relevance and methodological rigor. The review reveals that elevated CO2 levels are associated with respiratory symptoms, including coughing, wheezing, and shortness of breath, as well as the exacerbation of existing respiratory conditions. Additionally, exposure to increased CO2 concentrations can lead to respiratory acidosis, reduced lung function, and impaired gas exchange. Poorly ventilated indoor environments have been identified as potential hotspots for elevated CO2 levels, emphasizing the importance of monitoring indoor air quality. This review underscores the need for further research to elucidate the mechanisms underlying CO2-induced respiratory issues and to develop effective mitigation strategies. Understanding the correlation between CO2 and respiratory issues is crucial for public health interventions and policies aimed at minimizing the adverse impacts of elevated CO2 levels on respiratory health.